2008
DOI: 10.2137/145960606778644502
|View full text |Cite
|
Sign up to set email alerts
|

Feeding weaned piglets and growing-finishing pigs with diets based on mainly home-grown organic feedstuffs

Abstract: In 2000, EU regulations for organic animal production set new guidelines for organic pig feeding requiring that this be based on mainly home-grown organic feedstuffs. Doubts were however raised whether these feeding regimes can maintain good growth performance and carcass quality of pigs. Three experiments were carried out to study different organic feeding regimes in weaned piglets and fattening pigs. In Experiment 1, we evaluated the use of peas and faba beans (0, 120, or 240 g kg -1 ) in diets for wean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…In the finisher period (60-107 kg) the control pigs grew faster. Similar results were obtained by Partanen et al (2006) when blue lupine replaced rapeseed pressed cake at a level of 33%. In the earlier experiment of Hanczakowska and Świątkiewicz (2014) the mean daily body weight gains of fatteners fed with soybean meal (781 g) were intermediate between those of the pigs fed with blue (744 g) or yellow lupine (810 g) mixed with rapeseed press cake and these differences were not significant.…”
Section: Discussionsupporting
confidence: 83%
“…In the finisher period (60-107 kg) the control pigs grew faster. Similar results were obtained by Partanen et al (2006) when blue lupine replaced rapeseed pressed cake at a level of 33%. In the earlier experiment of Hanczakowska and Świątkiewicz (2014) the mean daily body weight gains of fatteners fed with soybean meal (781 g) were intermediate between those of the pigs fed with blue (744 g) or yellow lupine (810 g) mixed with rapeseed press cake and these differences were not significant.…”
Section: Discussionsupporting
confidence: 83%
“…The crude protein content was comparable to previous reports where the same pea variety was used (Partanen et al 2001, Partanen et al 2006. Cystine, lysine, methionine (only in case of enzyme unsupplemented diets) and threonine contents were the highest for diets that included peas up to 150 g kg -1…”
Section: Discussionsupporting
confidence: 85%
“…SBM. Several studies show the potential of these legumes as alternative protein sources for SBM in pig diets (Bohumila and Zdenek, 2009;Jezierny et al, 2010;Partanen et al, 2006;Van Nevel et al, 2000), although their use is limited due to their lower nutritional value and anti-nutritional factors. Literature data surveyed by Van Nevel et al (2000) showed that diets containing 4200 g of lupin seeds/kg of feed caused a lowered daily gain and feed intake in fattening pigs.…”
Section: Considered Dietsmentioning
confidence: 99%